2010
DOI: 10.1099/jmm.0.021691-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of human haemotropic Mycoplasma infections using a novel generic haemoplasma qPCR assay on blood samples and blood smears

Abstract: The aim of this study was to develop quantitative real-time (q)PCR assays to detect all known haemoplasma species, and a human housekeeping gene in order to demonstrate both successful DNA extraction from clinical samples and to test for sample inhibition, and to apply these qPCRs to human blood samples and blood smears. Sensitive and specific generic haemoplasma qPCR assays were developed to amplify haemoplasma species, as well as human glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as an internal amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 40 publications
(63 reference statements)
2
36
0
2
Order By: Relevance
“…(2) Bartonella henselae was evaluated by the method of Molia et al (2004). (3) General screening for hemoplasma DNA was done with a SYBR Green real-time PCR (Willi et al 2009), and positive samples were then tested with two hemoplasma group-specific TaqMan real-time PCRs (hemofelis vs. hemominutum groups; Tasker et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…(2) Bartonella henselae was evaluated by the method of Molia et al (2004). (3) General screening for hemoplasma DNA was done with a SYBR Green real-time PCR (Willi et al 2009), and positive samples were then tested with two hemoplasma group-specific TaqMan real-time PCRs (hemofelis vs. hemominutum groups; Tasker et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…For preliminary screening of hemoplasma infections, universal PCR primers for the hemoplasmas' 16S rRNA gene were used, as described by Tasker et al [16]. Real-time PCR was performed using a SmartCycler instrument (Cepheid, Sunnyvale, CA, U.S.A.) with SYBR Premix Ex Taq (Code #RR041A, TaKaRa Bio., Otsu, Japan).…”
mentioning
confidence: 99%
“…to invade erythrocytes exists in the literature; the possible concomitant presence of other pathogens able to invade erythrocytes cannot be ruled out. A possibility is the presence of hemoplasma, which are wall-less erythrocytic bacteria unable to be cultured in vitro, classified within the genus Mycoplasma, which have been described in human and animal infections [11]. However, an in silico analysis showed that the 16S rRNA universal primers used were able to amplify a fragment of 1,433 bp of the 16S rRNA gene of hemoplasma species (i.e., Candidatus Mycoplasma haemominutum, GeneBank access NC_021007.1).…”
Section: Discussionmentioning
confidence: 99%